Non-formal education in architecture: Latvian experience - Bratuškins, Uģis; Treija, Sandra; Babris, Matijs (Journal of Architecture and Urbanism, 2018)
A wide selection of informal and non-formal learning options has been developed during the last couple of decades by many schools of Architecture and non-educational bodies to accumulate creative potential of students and give them the opportunity to express themselves in alternative learning environments. These options include summer schools, short-term brainstorming actions, competitions, and other activities focusing on interdisciplinary approach, teamwork and intense discussions with professionals from various fields not directly involved in the formal education process.Considering high popularity of non-formal learning activities and many students involved, it is important to evaluate the respective experience to estimate whether and how abilities and skills acquired through non-formal learning could benefit to those requested by the formal education programmes.The paper discusses the role and methods of non-formal education in Architecture with an aim to identify particular goals achieved using each form of learning. The case study presented in the paper is based on more than 12 years’ experience accumulated by Riga Technical University, Faculty of Architecture, in organizing non-formal educational courses for the students of Architecture and the related fields considering the experience students gained participating in the activities organized by themselves or other parties.